Numerical study on the punching shear strength of edge steel-reinforced concrete slab-column connections - Ahmed Gouda (Results in Engineering, 2025)
Punching shear failure in steel-reinforced concrete (RC) edge slab-column connections poses a critical challenge in structural engineering, with safety and design efficiency implications. This study investigates the influence of key geometric parameters—slab thickness, column aspect ratio, square column stub size, and span-to-depth ratio—on punching shear strength, a topic underexplored in existing research. A unique feature of this research is the ability to examine the effects of slab thickness, column aspect ratio, and square column stub size independently, without any interference from changes in the span-to-depth ratio, by keeping it constant. This approach has never been achieved before and is impractical in experimental studies. Using finite element modeling, over 20 connection configurations were analyzed to assess their structural behavior. Results showed that increasing slab thickness reduced deflection by up to 95 % but decreased punching shear strength by 40 % due to stress redistribution. Higher column aspect ratios and larger square column stubs caused strength reductions of 36 % and 43 %, respectively, while reducing the span-to-depth ratio enhanced stiffness and punching shear strength by 25 %. The study also evaluated the accuracy of three design standards—American (ACI 318–19 (22)), Canadian (CSA-A23.3:24), and Japanese (JSCE-2007)—revealing deviations of up to 144 % from actual performance. To address these discrepancies, four new equations were proposed, tailored to specific geometric parameters, and validated against available literature, demonstrating superior accuracy compared to existing standards. These findings underscore the limitations of current methodologies and emphasize the importance of incorporating geometric factors to improve slab-column connection designs in modern construction.